Melt Compounding of Thermoplastic Polyurethanes Incorporating 1D and 2D Carbon Nanofillers. Issue 7 (3rd May 2017) - Yuan, Dian; Pedrazzoli, Diego; Pircheraghi, Greza; Manas-Zloczower, Ica
ABSTRACT: Thermoplastic polyurethane nanocomposites incorporating carbon nanotubes and graphene nanoplatelets were prepared through melt blending and compression molding, and the compounding process was optimized taking into account the different physical properties of one-dimensional carbon nanotubes and two-dimensional graphene nanoplatelets. Filler dispersion was further improved in the case of carbon nanotubes by noncovalent surface modification using a specific surfactant. The well-dispersed nanofillers favored enhanced phase separation in the thermoplastic polyurethane, leading to a better microstructure, which is able to improve the load transfer and maximize the tensile and viscoelastic properties. GRAPHICAL ABSTRACT: